Malay Language Teaching And Learning Strategy Among International Students At Universiti Malaysia Pahang = Strategi Pengajaran Dan Pembelajaran Bahasa Melayu Dalam Kalangan Pelajar Antarabangsa Di Universiti Malaysia Pahang - Juwairiah, Osman; Jamilah Bebe, Mohamad; Anis Nabilla, Ahmad; Jamal Rizal, Razali (Universiti Pendidikan Sultan Idris, 2018)
The teaching and learning of Malay language to international students was conducted in all public and private universities. This course is generally aimed at promoting the Malay language to international students to help them communicate throughout their stay in Malaysia. This study will highlight the teaching and learning strategies used by lecturers and international students at Universiti Malaysia Pahang (UMP) in teaching and learning Malay language. To discuss the effectiveness of the strategy, the researcher used the theory of learning introduced by Kolb (1984). According to this theory, experiential learning will help and accelerate the improvement of individual cognitive skills involving the acquisition of abstract concepts through involvement in various situations. Kolb (1984) uses the term concrete experience, reflective observation, abstract conceptualization and active experiment. The data was collected from students’ answers of the practices in the Malay Language Module and from observations in the various activities used throughout the course. In addition, a questionnaire was also given to students to evaluate the effectiveness of teaching and learning methods as suggested by Kolb Theory (1984). Results from analysis show that teaching and learning strategies based on topics related to students’ life experience are effective to help them master and speak the Malay language.